THEORETICAL RATIONALE FOR THE SELECTION OF THE OPTIMAL SCHEME OF SEPARATION OF THE THREE-COMPONENT MIXTURE - M. K. Zakharov; Yu. A. Pisarenko (Тонкие химические технологии, 2017)
It is theoretically justified that for the scheme of separation of three-component mixtures with the release of the high-boiling component in the first column there is a region of initial compositions for which the heat costs are the least. An expression describing the boundary of the optimality regions of different separation schemes is given. The calculation of the heat costs for both rectification schemes of the three-component mixtures performed using the Aspen Plus software package confirmed the theoretical justification for the existence of optimality regions for each of them. With the help of the concept of internal energy saving, the advantage of one or another scheme of separation of a three-component mixture is explained.